Synergic emissions reduction effect of China's "Air Pollution Prevention and Control Action Plan": benefits and efficiency - Yang, Xiaohui (2023)
Large amounts of fossil fuels that are consumed in association with the urbanization process, lead to billions of tons of greenhouse gases and air pollutants. Air pollution control policies have the synergic effects on carbon emissions reduction, but whether they can improve the synergic emission reduction efficiency (SERE) needs to be studied. 279 Chinese cities are selected as research samples. We evaluate the synergic effect of China's "Air Pollution Prevention and Control Action Plan" (APPCAP) from the perspectives of benefits and efficiency with the Difference-in-differences (DID) model. We further decompose the SERE into synergic emission reduction technological efficiency change (SEREEC) and synergic emission reduction technological change (SERETC) to analyze the internal impact mechanisms. The result shows that: (1) SERE has increased by 8 % from 2010 to 2017, for the expansion of the possibility boundary. (2) The APPCAP has co-benefit of carbon emissions reduction by 1.5 %, but inhibits the SERE increase by 1.2 % because of the lack of resource allocation efficiency improvement. (3) The APPCAP has an inhibitory effect on SEREEC and a promoting effect on SERETC. Therefore, the government should emphasize the source control and treatment efficiency, and further strengthen the system innovation for achieving urban sustainable development effectively.